Relaciones entre eventos: la codificación de Manera (-s) en quichua santiagueño (Signo y seña, 2017)
Santiagueño Quechua has a switch-reference system with suffixes that indicate different subject (DS), -pti, and same subject (SS) -s and -spa. The literature on the subject has indicated that the two SS suffixes were allomorphs, being -s the shorter form of -spa (Nardi 2002, Albarracín de Alderetes 2016). However, the speakers do not select both SS suffixes interchangeably. The main hypothesis of this article is that these two suffixes establish different event relations: -spa, marks laxer relations, and -s, introduces Manner clauses, i.e. closer relations. In order to state the hypothesis, it is proposed here a distribution of the switch-reference suffixes in an inter-clausal semantic continuum (Van Valin 2005), where ‘Manner’ is located at the narrowest end. At the same time, this semantic relation between events has a syntactic correlate. Therefore, it is also established here a “desententialization” continuum (Lehmann 1988) with ‘sentential’ and ‘nominal’ ends, where -s clauses are located at the “desententialized” end. Thus, the clauses introducing Manner in Santiagueño Quechua constitute a complex state of affairs: syntactically, as compression (Lehmann 1988), and semantically, as a macroevent (Talmy 2000).